2016
DOI: 10.1016/j.rgg.2015.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Chalcophile elements in black shales of the Bazhenov Formation, West Siberian sea basin

Abstract: The contents and distribution of chalcophile elements in the Upper Jurassic-Lower Cretaceous Bazhenov Formation (black shales), West Siberian sea basin, are related to the composition of rocks, sedimentation rate, and redox conditions of sedimentation. The total content of chalcophile elements in the argillaceous-siliceous and argillaceous mudstones of normal sections (1360.7 and 498.4 ppm, respectively) is higher than the clarkes for black shales of this type, while that in the silty argillaceous mudstones of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(13 reference statements)
0
0
0
Order By: Relevance
“…The Upper Jurassic-Lower Cretaceous deposits of the Formation (J 3 -K 1 ) are distributed throughout the West Siberian oil and gas Basin, covering over 1 million km 2 . These deposits occur at depths of 2500-3000 meters between Upper Jurassic terrigenous rocks and Lower Cretaceous mudstones [16][17][18]. The thickness of the formation varies from 25 to 80 m, with an average of 30-40 m. The rocks are represented by siliceous, clayey-siliceous, carbonate, and clayey-carbonate-siliceous varieties with high organic matter (OM) content [19,20].…”
Section: Regional Settingsmentioning
confidence: 99%
“…The Upper Jurassic-Lower Cretaceous deposits of the Formation (J 3 -K 1 ) are distributed throughout the West Siberian oil and gas Basin, covering over 1 million km 2 . These deposits occur at depths of 2500-3000 meters between Upper Jurassic terrigenous rocks and Lower Cretaceous mudstones [16][17][18]. The thickness of the formation varies from 25 to 80 m, with an average of 30-40 m. The rocks are represented by siliceous, clayey-siliceous, carbonate, and clayey-carbonate-siliceous varieties with high organic matter (OM) content [19,20].…”
Section: Regional Settingsmentioning
confidence: 99%
“…Differences in sedimentation conditions and initial organic matter type in the central and peripheral areas led to the formation of the Bazhenov deposits with different lithological characteristics, total organic carbon (TOC) distribution, composition, and petroleum generation potential. The results of the studies of the Bazhenov Formation rocks and organic matter are reported in numerous publications, including the marine sediments of the central part (distal areas of the paleo-sea) [1,[4][5][6][7][8][9] and sediments formed in the peripheral parts (proximal paleo-sea areas) [1,5,7,[10][11][12][13][14]. Although data have been extensively published, there is still a potential for deepening the knowledge via application of the scope of analytical methods and investigation of the least studied areas.…”
Section: Introductionmentioning
confidence: 99%
“…The interval investigated includes the Bazhenov Formation and upper part of the Abalak Formation deposits from the Oxfordian stage of the Upper Jurassic to the Berriasian of the Lower Cretaceous (Figure 1). [4]) and stratigraphy of Mesozoic deposits (modified after Afanasenkov [14]); the investigated stratigraphic interval is marked by frame.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation